Blockchain technology in smart contracts for refueling civil aviation aircraft - V. V. Gordeev; O. V. Gromov; V. K. Gromov; G. I. Litinsky; V. M. Samoylenko (Научный вестник МГТУ ГА, 2021)
In the process of air transportation, a large amount of information exchange plays an important role in the timely management of aircraft flights. The work of any airline and airport consists of many processes that involve a big number of participants. One of these issues is timely aircraft refueling. The use of the blockchain technology makes it possible to process an airline request for aircraft refueling in a timely manner, make payment and exchange of accounting documents between the airline and the refueling complex. The paper gives the main definitions for the elements of the smart contracts and their interrelationships based on the blockchain technology when performing accounting operations and payment transactions for aircraft refueling. The article is devoted to a comprehensive study of the smart contract technology application in the aircraft refueling system, in particular, the exchange of accounting and payment documentation between the airline, the refueling complexes of civil aviation airports and banks. The aim of the research work is to study the application of the blockchain technology in the aircraft refueling operations. Based on the analysis it is necessary to develop a scheme for the use of the smart contract technology when aircraft refueling, which allows the parties concerned to reduce the volume of accounting and payment operations and increase the operating efficiency of the objects and subjects of the refueling process. The paper presents the chain of information passing and blockchain transformation varying from the execution of refueling operations to the execution of banking operations, payment for jet fuel and related services for aircraft refueling. Special attention is paid to the role and location of aircraft refueling facilities as a key element of the module for automatic reconciliation of accounting and payment documents in the formation of a smart contract. Based on the analysis of the blockchain technology application, a scheme of interaction among an airline, a refueling complex and a bank is proposed. The application of the proposed scheme allows the airline to pay for refueling at the time of refueling without time-consuming accounting operations and prepayment for jet fuel, thereby reducing the accounting time.